The Source of Daniel’s Animal Imagery - Lucas, Ernest (Tyndale bulletin, 1990)
An evaluation of a number of suggestions concerning the source of the animal imagery in Daniel 7-8 considering implications for the authorship, date and provenance of these chapters.